The reception of the legend of Hero and Leander - Murdoch, Brian, 1944- (Brill's Companions to Classical Reception;, 2019)
This book is a study of the literary reception of the originally Greek love-story of Hero and Leander, examining the nature of the tale and demonstrating its longevity and huge popularity from classical times to the present, in a great variety of different genres. Chapters consider the classical versions (Ovid, Musaios, Martial), medieval and renaissance versions in various European languages, folk and literary ballads (and even a pop song), the lyric, dramatic versions, settings to music, burlesques and travesties in all genres, modern reflections of the story in (experimental) literary forms.